The moral culture of the Scottish enlightenment 1690–1805 by Thomas Ahnert (Review) - Mills, R. J. W. (2020)
This engaging work is a significant contribution to scholarship both on the Scottish Enlightenment and on the relationship between the European Enlightenment and religion. Writing with persuasive acuity, Ahnert examines how over the course of the eighteenth century a shift in emphasis occurred in Scottish theology away from doctrinal orthodoxy and toward moral conduct as the true measure of piety. The stress that leading clerical figures of the Scottish Enlightenment put on pious action was bound up with a skeptical reclassification of the capacity of unassisted reason to achieve epistemic certainty in doctrinal matters. These clergymen wanted to get away from the orthodox idea of salvation sola fide, which viewed good conduct as a secondary element of Christianity. The Moderates, the key grouping of “enlightened” clergymen who emerged by the 1750s, encouraged piety and virtue through recommending the “culture of the mind.” The term “culture” was used as meaning the process of cultivation: the incremental improvement of the moral and religious character of an individual through scripture-inspired practice. To avoid “papism,” however, the Moderates maintained that divine support was still necessary for salvation. Ahnert purposefully presents us with a paradox in the process of cultivation: orthodox Presbyterians maintained the existence of natural religion resulting unavoidably from the act of reasoning, whereas the Moderates believed that religious tenets were achievable through access to divine revelation and were of secondary importance to pious behavior.